Endogenous pluripotent factor expression after reprogramming cat fetal fibroblasts using inducible transcription factors. Issue 11 (19th August 2019) - Zhou, Ran; Comizzoli, Pierre; Keefer, Carol L.
Abstract: Incomplete transgene‐silencing remains a challenge in the generation of induced pluripotent stem cells (iPSC) in felids—a critical family in biomedical and biodiversity conservation science. In this study doxycycline‐inducible transgenes ( NANOG, POU5F1, SOX2, KLF4, and cMYC ) were used to reprogram cat fetal fibroblasts with the objective of obtaining iPSC with fully silenced transgenes. Colony formation was slower (14 vs. 8 days) and at lower efficiency than mouse embryonic fibroblasts (0.002% vs. 0.02% of seeded cells). Alkaline‐phosphatase positive colonies were grown on feeder cells plus LIF and GSK3, MEK, and ROCK inhibitors. Cells could be passaged singly and transgene expression was silenced at passage 3 (P3) after doxycycline removal at P2. NANOG, POU5F1, and SOX2 were expressed at P3, P6, and P10, although at lower immunostaining intensities than in cat inner cell masses (ICM). Transcripts related to pluripotency ( NANOG, POU5F1, SOX2, KLF4, cMYC, and REX1 ) and differentiation ( FGF5, TBXT, GATA6, SOX17, FOXF1, PAX6, and SOX1 ) were assessed by a reverse transcription‐quantitative polymerase chain reaction in iPSC and embryoid bodies. The immunostaining patterns, relatively low levels of NANOG and REX1 in comparison to ICM along with the expression of TBXT (mesoderm) suggested that cells were a mix of reprogrammed pluripotent and differentiating cells. Abstract : Pluripotent‐like colonies could be generated from cat fetal fibroblasts using a drug‐inducible system expressing human transcription factors. These transgenes were silenced upon doxycycline removal. Endogenous pluripotency‐related genes (NANOG, POU5F1, SOX2, and REX1) were expressed and reprogrammed cells could be passaged singly for over ten passages.